Computer literacy among college students of the UP in the Visayas - Pasamanero, Catherine O.; Setiar, Benett G.; Subebe, Alexina D.; Togonon, Margret M. (1996)
The major findings of this investigation were as follows: 1. Generally, the computer literacy level of students in the University of the Philippines in the Visayas is average. 2. No significant relationship exists between the computer literacy level of students and the monthly income that the family recieved. Findings show that wether the respondents belong to the lower income or higher income they are average in terms of computer literacy. 3. Significant relationship exists between the literacy level and the college in which the respondents have enrolled. Conclusions : 1. Generally, the computer literacy level of students in the University of the Philippines in the Visayas is average. 2. The computer literacy level of students is not significantly associated with the monthly income of the families to which they belong. Implications: The implication of this investigation are discussed below with the purpose of providing the students, teachers, school administrators and higher officials of the National Computer Center and the Department of Education culture and sports necessary insights for further improvement of computer education. 1. One of the findings of the study indicates that the computer literacy level of the students is average. This may imply that the literacy level of students can still be the improve. Hence, the school administrators as well as the computer instructors of the school may look into the factors that could further improve the literacy level of students. 2. Another finding of this study reveals that the computer literacy level of the students is not significantly related to the monthly income of the families in which they belong. Thus, the family income should not be considered as a requisite in learning. Recommendation: In view of the findings of this investigation the following recommendations are set forth for consideration. 1. The policy makers of the National Computer Institute and the curriculum planners of the Bureau of Higher education and the Department Of Education Culture and Sports may consider the finding of this study when undertaking appropriate means towards development and improvement of the curriculum in computer education, specifically in terms of determining the optimal balance between the time allotted to theory and practical work. The allotted computer hands-on time should be increased from the minimum to the maximum. 2.School administrators and supervisors should strengthen supervising practices so as to see to it that instructors and students make full use of allotted class time for hands-on in order to improve the literacy level of students. 3. For further researchers, a study on the performance of computer instructors in relation to their academic and technical preparation and the existing facilities of the school. The group was not able to investigate on this matter because of time constraint.
Research Paper (Mgt 200 - Management Research) -- Iloilo City : UPV-CM, March 27, 1996